A meta-analysis of the association between CTLA-4 genetic polymorphism and susceptibility of asthma. Issue 28 (July 2018) - Zheng, Yan; Wang, Hongluan; Luo, Linlin; Liao, Liyang; You, Luxia; Wang, Jun; Li, Qiugen
Abstract: Background: Numerous studies have reported an association between cytotoxic T-lymphocyte associated antigen 4 gene ( CTLA4 ) polymorphism and susceptibility to asthma, in different populations, but the results have been inconsistent. We performed a meta-analysis of 19 published case–control studies to obtain a reasonably accurate estimation of the relationship between CTLA4 polymorphism and asthma. Methods: We searched the Pubmed, EMBASE, Chinese National Knowledge Infrastructure, and Wanfang databases and extracted data from 19 independent, eligible studies. Odds ratios (ORs) with 95% confidence intervals (CIs) and Egger test were separately used to assess the strength of associations and publication bias. Results: A total of 19 case–control studies involving 4831 cases and 4534 controls were identified. The combined results revealed that there was significant association between the +49A/G polymorphism and asthma (for GG + GA vs. AA: OR = 0.82, 95% CI = 0.70–0.97, P = .02). Stratification by race or age indicated a significant association between the CTLA-4 +49 GA+GG genotype and asthma in Asians (OR = 0.80, 95% CI = 0.68–0.95, P = .01) and children (OR = 0.75, 95% CI = 0.62–0.90, P = .002), but there was no association in whites (OR = 0.94, 95% CI = 0.80–1.10, P = .44) and adults (OR = 0.85, 95% CI = 0.68–1.06, P = .15). Additionally, there was a significant association with atopic asthma under the random-effects model (OR = 0.81, 95% CI = 0.67–0.98, P = .03). In addition, there was no significant association between the −318 C/T polymorphism and asthma risk. Conclusions: Our meta-analysis results suggested that the +49A/G polymorphism in CTLA-4 was an important risk factor for asthma susceptibility, especially in Asian individuals, children, and atopic patients.